2020
DOI: 10.1017/s0007123420000393
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Probity: Anticorruption and Adverse Selection in the Chinese Bureaucracy

Abstract: Fighting corruption is often seen as a crucial step toward building better institutions, but how it affects political selection remains less well understood. This article argues that in systems where corruption functions as an informal incentive for government to attract talent, anticorruption initiatives that curb rent-seeking opportunities may unintentionally weaken both the quality and the representativeness of the bureaucracy. The authors test this argument in China using an original nationwide survey of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…My research, however, highlights that by altering the underlying distribution of power, corruption can contribute to strengthening institutions instead. It thus adds to a recent strand of literature applying a more nuanced view to these practices, especially in the context of authoritarianism (e.g., Jiang 2018; Jiang et al 2022; Demarest 2021; Collord 2022). In combination with this line of research, my work points to the need to study the consequences of corruption in authoritarian regimes more systematically.…”
Section: Introductionmentioning
confidence: 95%
“…My research, however, highlights that by altering the underlying distribution of power, corruption can contribute to strengthening institutions instead. It thus adds to a recent strand of literature applying a more nuanced view to these practices, especially in the context of authoritarianism (e.g., Jiang 2018; Jiang et al 2022; Demarest 2021; Collord 2022). In combination with this line of research, my work points to the need to study the consequences of corruption in authoritarian regimes more systematically.…”
Section: Introductionmentioning
confidence: 95%
“…For example, a recent study of civil servants in the health sector of a low-income country found an empirical correlation between competence and corruption: the individuals who paid the largest bribes to acquire a civil service position were also the most capable (Weaver, 2021). Similarly, Jiang, Shao, & Zhang (2022) argue that anti-corruption efforts may dissuade high-quality candidates from entering the civil service.…”
Section: Main Hypothesis: Democratization Increases the Promotion Pre...mentioning
confidence: 99%
“…First, personal connections (e.g., shared hometown, college or former workplaces) with the top leaders in central government are believed to have an important influence on the career development of political elites in contemporary China (Shih et al, 2012;Jia et al, 2015). Such personal connections are in turn a crucial factor in the decision to investigate a potentially corrupt high-ranking official (Jiang et al, 2022). This means TH is more of a person-specific event than a regional event.…”
Section: China's Anti-corruption Campaignmentioning
confidence: 99%
“…There is an emerging literature on the effects of disclosing anti-corruption information on corruption and voting behaviour (Ferraz & Finan, 2008;Cavalcanti et al, 2018;Avis et al, 2018;. Some studies have analysed the impact of the current anti-corruption campaign in China on related outcomes, such as corruption-related rent-seeking (Chen & Kung, 2019), political support (Wang & Dickson, 2022), civil servant recruitment (Jiang et al, 2022) and different corporate behaviours (e.g., Xu & Yano, 2017;Hao et al, 2020;Xu et al, 2021). Others shed light on whether investigating high-ranking officials will reduce or, inversely, increase actual corruption from a purely theoretical angle (Che et al, 2019).…”
Section: Introductionmentioning
confidence: 99%